2022
DOI: 10.3390/s22082903
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Horse-Riding Simulator with Virtual Reality on Gross Motor Function and Body Composition of Children with Cerebral Palsy: Preliminary Study

Abstract: This study aimed to evaluate the effect of a horse-riding simulator (HRS) with virtual reality (VR) on gross motor function, balance control, and body composition in children with spastic cerebral palsy (CP). Seventeen preschool and school-aged children with spastic CP were included; 10 children in the intervention group (HRS group) received 30 min of HRS with VR training twice a week for a total of 16 sessions in addition to conventional physiotherapy. Seven children in the control group were instructed to pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 31 publications
0
32
0
1
Order By: Relevance
“…Twenty-one studies were deleted for not meeting the inclusion criteria (reasons in Figure 1 ). Finally, 12 clinical trials were included in this review [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. All studies provided data for the qualitative synthesis (systematic review), and 10 reported quantitative data for use in the quantitative synthesis (meta-analysis) [ 63 , 64 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-one studies were deleted for not meeting the inclusion criteria (reasons in Figure 1 ). Finally, 12 clinical trials were included in this review [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. All studies provided data for the qualitative synthesis (systematic review), and 10 reported quantitative data for use in the quantitative synthesis (meta-analysis) [ 63 , 64 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…The studies included in this review were conducted between 1998 and 2022 in India [ 64 , 67 ], South Korea [ 65 , 66 , 70 , 71 ], Iraq [ 63 ], Spain [ 69 ], Brazil [ 73 ], Thailand [ 74 ] and the USA [ 72 ]. The included studies reported data from 343 patients with spastic diplegic CP with ages between 2 and 16 years old, of which 56% were male versus 44% female.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [29], the researches uses a HRS device, a HMD to provide an immersive VR experience and a pair of hand-tracking device for controlling the VR game content. Each session consists of the following cycle: warm-up, first training program, rest period, second training program, and cool down for a total of about 30 minutes.…”
Section: Related Workmentioning
confidence: 99%
“…Other popular option is OSIM uGallop (Taiwan), used by 3 teams of researchers [18,23,24]. Lastly, SRIDER (Neiplus,Korea) [15], Shinhwa (Korea) [25], and Jufit JFF043QM (China) [26] each used by 1 team of researcher. However, all of the store-bought HRS devices have a similar design.…”
Section: Related Research and Contribution Of Our Workmentioning
confidence: 99%